An experimentally validated study for open rib profiles steel‐concrete composite slabs behavior in partial connection. Issue 3 (16th September 2019) - Soltanalipour, Milad; Ferrer, Miquel; Marimon, Frederic
ABSTRACT: In this paper the strength of steel deck‐concrete composite slabs is studied. Conventional slabs with open and dovetail profiles are studied with different designs, galvanized and stainless steel. Partial connection method (PCM) in Eurocode‐4 is permitted for slabs with ductile longitudinal shear behavior. Ductility, as explained in the clause 9.7.3(3), depends on the fact that the failure load exceeds the load corresponding to the slip (0.1 mm) in more than 10%; then the slab is classified as ductile. Apparently, the aim of this criterion is to ensure the slab can undergo further deflections until the whole yielding of the cross‐section is achieved, as required hypothesis by the PCM. The aim of this paper is to study the stresses developed at the cross‐section of composite slabs with open and dovetail profile, in order to evaluate the yielding degree of the cross‐section. Based on the results of this study, it is recommended to exclude open profiles from partial connection method (PCM), even if the slab is classified as ductile through Eurocode definition. Although all studied specimens are classified as ductile according to Eurocode‐4 clause 9.7.3(3), the observed stress distribution at cross‐section proves that yielding occurs in the slab with re‐entrant profile only, whereas slabs with open‐rib profiles remain almost elastic until their brittle failure.